INFRAESTRUCTURA DE TRANSPORTE EN EL ASIA-PACÍFICO: DEMANDA FUTURA, PROBLEMAS Y SOLUCIONES - Kim, Joseok (1997)
The economy of the Asia-Pacific region has registered one of the highest growth rates and this trend is expected to continue. As a result, passenger and cargo traffic has also increased, causing most of the airports and ports to become congested. This has generated the need for the State to invest in new infrastructure that can meet current demand, but the construction of new ports and airports generates a series of challenges, including financing, ownership, administration and regulation; all this in a globalized context, of economic liberalization and integration. The problems presented by the operation and investment in infrastructure, their causes and the possible ways of solving them are reviewed, at the same time that two policy options are presented: planning mechanisms and market mechanisms. Different options for introducing the market mechanism into infrastructure are examined, such as deregulation, the management contract, the effects of the reform, and the role of the government.